1997
DOI: 10.1128/jb.179.13.4399-4402.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thiI, a new gene involved in thiazole biosynthesis in Salmonella typhimurium

Abstract: Thiamine pyrophosphate (TPP) is a required cofactor in Salmonella typhimurium that is generated de novo by the condensation of 4-amino-5-hydroxymethyl pyrimidine (HMP) pyrophosphate and 4-methyl-5-(␤-hydroxyethyl)-thiazole (THZ) monophosphate. The THZ and HMP moieties are independently synthesized, and labeling studies have demonstrated probable metabolic precursors to both. We present herein the initial characterization of thiI, a gene required for THZ synthesis. We show that thiI is a 1,449-bp open reading f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…1) (17). The thiI gene was shown to be required for s 4 U synthesis in E. coli by Mueller et al (18) and for thiazole biosynthesis in Salmonella typhimurium by Webb et al (19). We later found that the cysteine desulfurase IscS was required for s 4 U synthesis both in vitro (20) and in vivo (21) and demonstrated in vitro s 4 U synthesis with an unmodified tRNA substrate.…”
mentioning
confidence: 77%
“…1) (17). The thiI gene was shown to be required for s 4 U synthesis in E. coli by Mueller et al (18) and for thiazole biosynthesis in Salmonella typhimurium by Webb et al (19). We later found that the cysteine desulfurase IscS was required for s 4 U synthesis both in vitro (20) and in vivo (21) and demonstrated in vitro s 4 U synthesis with an unmodified tRNA substrate.…”
mentioning
confidence: 77%
“…The iscS Ϫ strain did not grow in M9/glucose or M63/glycerol minimal media supplemented with leucine (parent strain MC1061 is a leucine auxotroph). Because of earlier reports (12)(13)(14) on the relationship between s 4 U and thiamin biosynthesis and our recent work, we suspected that thiamin was also necessary for growth. However, addition of thiamin to the minimal medium was insufficient for growth.…”
Section: Construction Of the Iscsmentioning
confidence: 99%
“…Interestingly, the nuvC mutant, which lacked s 4 U in its tRNA, also required thiamin for growth in minimal media (12). The thiI gene was recently identified as a requirement for both s 4 U (13) and thiamin synthesis (16) in E. coli and for thiazole biosynthesis in Salmonella typhimurium (14).…”
mentioning
confidence: 99%
“…By using the same genetic screen, we identified the gene thiI as essential for s 4 U formation (25) shortly after Downs and co-workers (26) identified the same gene as essential for thiamin biosynthesis. We have cloned and overexpressed thiI from E. coli (25).…”
mentioning
confidence: 99%